Study on students’ gender, study styles and study hours in exam performances related to Neuro-Linguistic Programming - Mohamad, Nurhana; Hassanor, Siti Norsyahirah; Azman, Nazihah; Mansor, Norshawanie (Penerbit UTHM, 2020)
Neuro-Linguistic Programming describes the fundamental dynamics between mind (neuro) and language (linguistic) and how their interplay affects our body and behavior programming). We conducted this project by relating NLP in students’ study styles. There were a few factors that influenced Grade Point Average (GPA) which are gender, study styles and study hours.